Pengaruh Sikap dan Pengetahuan Tentang Bahaya Merokok Terhadap Perilaku Merokok Mahasiswa STIKes PHI Tahun 2016 - Siska Toto; Revie Fitria Nasution (Jurnal Persada Husada Indonesia, 2016)
Smoking has become a normality found wherever we are. Smoking is a habit that is widely practiced in both educated & otherwise environments. Each cigarette contains over 4000 chemicals harmful to the body, 400 of them can have toxic effects, while 40 of them can cause cancer. Persons with smoking behaviour usually find it hard to quit. Many late teens between ages of 21-24 years of age are only followers as they are just adhering to the smoking trend eventhough they are aware of the effects of smoking. According to Riskesdas 2013 report, analysis results showed a slight increase in the public smoking perportional rate especially in children and juveniles aged between 15 to 29 years of age. The rate increase can be seen from the years 2007 to 2013 from 23,7% to 24,3%. DKI Jakarta ranked 12th position as a province with massive porportion of 23,2 % of smokers population. The aim of this study was to analyse the influence of knowledge, attitudes and characteristics towards smoking behaviour. This study applied cross sectional approach on 94 respondents through data collection. Data processing used chi-square test (@ = 0,05). A few study results showed no knowledge and characterictic (age, parents’ careers and monthly allowances) influnces towards smoking behaviour in male undergrads aged between 18-30 years of age with value of p = > 0,05. Study results also showed the presence of influence between attitude, characteristics (peer role) towards smoking behaviour with value of p = < 0,05.